2019
DOI: 10.3390/polym11061016
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Platelet-Rich Plasma to Promote Cell Recruitment into Low-Molecular-Weight Fucoidan-Functionalized Poly(Ester-Urea-Urethane) Scaffolds for Soft-Tissue Engineering

Abstract: Due to their elastomeric behavior, polyurethane-based scaffolds can find various applications in soft-tissue engineering. However, their relatively inert surface has to be modified in order to improve cell colonization and control cell fate. The present study focuses on porous biodegradable scaffolds based on poly(ester-urea-urethane), functionalized concomitantly to the scaffold elaboration with low-molecular-weight (LMW) fucoidan; and their bio-activation with platelet rich plasma (PRP) formulations with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 92 publications
(137 reference statements)
2
13
0
Order By: Relevance
“…2 A). Therefore, no significant difference was found between the platelet count in these biotechnological products, which coincides with the data of some studies on plateletrich plasma [36,40,43,47]. However, some studies have shown that the number of platelets in leukocyte-poor platelet concentrates is significantly lower than in leukocyte-containing ones [6,39].…”
Section: Resultssupporting
confidence: 85%
“…2 A). Therefore, no significant difference was found between the platelet count in these biotechnological products, which coincides with the data of some studies on plateletrich plasma [36,40,43,47]. However, some studies have shown that the number of platelets in leukocyte-poor platelet concentrates is significantly lower than in leukocyte-containing ones [6,39].…”
Section: Resultssupporting
confidence: 85%
“…However, tissue-engineering based bone regeneration continues to face considerable challenges. While ideally porous scaffold materials should mimic the extracellular matrix (ECM) of native tissue in order to ensure adequate nutrient and oxygen diffusion, waste product removal as well as cellular infiltration and vascularization, the scaffold(s) must also have adequate mechanical integrity to cope with its environment, possess an appropriate biodegradation profile and minimise any host inflammatory response during the regenerative process [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…270 Since then, it has also been used as a cell culture supplement for the expansion of stem and progenitor cells for tissue engineering applications in the context of muscule, 271 bone, 272 cartilage, 273 skin, 274 and soft tissue repair. 275 PRP contains a mix of different cytokines and GFs, including platelet-derived growth factor (PDGF) which is a protein that stimulates the proliferation and synthesis of new collagen formation; TGFβ-1 that counteracts the catabolic effects of IL-1 on tissues such as cartilage, by increasing chondrocyte synthesis as well as by increasing ECM production; FGF that is able to promote tissue healing by activating anabolic pathways; and finally hepatocyte growth factor (HGF) which increases tissue repair by promoting angiogenesis, as well as chemotaxis of MSCs, along with subchondral progenitor cells to promote chondral matrix formation and remodeling. 269 Due to their high GFs content in platelet, PRP has been shown to improve cell growth in different research studies.…”
Section: Recellularization Of Cartilagementioning
confidence: 99%
“… 270 Since then, it has also been used as a cell culture supplement for the expansion of stem and progenitor cells for tissue engineering applications in the context of muscule, 271 bone, 272 cartilage, 273 skin, 274 and soft tissue repair. 275 …”
Section: Introductionmentioning
confidence: 99%